All maximal idempotent submonoids of HypG(2) - Weerapong Wongpinit (2018)
The purpose of this paper is to determine all maximal idempotent submonoids and some maximal compatible idempotent submonoids of the monoid of all generalized hypersubstitutions of type τ = (2).